2022
DOI: 10.3390/ijms23010524
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Antimicrobial Effects of Hybrid Peptides Synthesized Based on the Sequence of Ribosomal S1 Protein from Staphylococcus aureus

Abstract: The need to develop new antimicrobial peptides is due to the high resistance of pathogenic bacteria to traditional antibiotics now and in the future. The creation of synthetic peptide constructs is a common and successful approach to the development of new antimicrobial peptides. In this work, we use a simple, flexible, and scalable technique to create hybrid antimicrobial peptides containing amyloidogenic regions of the ribosomal S1 protein from Staphylococcus aureus. While the cell-penetrating peptide allows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 71 publications
0
17
0
2
Order By: Relevance
“…Our study showed that Sarmodified peptides exhibit a wide range of antimicrobial activity against MRSA, P. aeruginosa, E. coli, and B. cereus [36]. As a result of the series of experiments, the minimum inhibitory concentrations (MICs) of the modified peptides were determined against strains of pathogenic methicillin-resistant S. aureus (MRSA), S. aureus, and P. aeruginosa (Table 2) [35,36]. As follows from Table 2, we found that the antimicrobial effect of the same peptides against various pathogenic microorganisms is comparable to the MIC (~1-5 µM) of the commercial antibiotic gentamicin sulfate [116,117].…”
Section: Antibacterial Activity Of Hybrid Amyloidogenic Peptidesmentioning
confidence: 68%
See 4 more Smart Citations
“…Our study showed that Sarmodified peptides exhibit a wide range of antimicrobial activity against MRSA, P. aeruginosa, E. coli, and B. cereus [36]. As a result of the series of experiments, the minimum inhibitory concentrations (MICs) of the modified peptides were determined against strains of pathogenic methicillin-resistant S. aureus (MRSA), S. aureus, and P. aeruginosa (Table 2) [35,36]. As follows from Table 2, we found that the antimicrobial effect of the same peptides against various pathogenic microorganisms is comparable to the MIC (~1-5 µM) of the commercial antibiotic gentamicin sulfate [116,117].…”
Section: Antibacterial Activity Of Hybrid Amyloidogenic Peptidesmentioning
confidence: 68%
“…In addition, modified peptides can provide a longer duration of action, as they are more resistant to proteases. Our study showed that Sarmodified peptides exhibit a wide range of antimicrobial activity against MRSA, P. aeruginosa, E. coli, and B. cereus [36]. As a result of the series of experiments, the minimum inhibitory concentrations (MICs) of the modified peptides were determined against strains of pathogenic methicillin-resistant S. aureus (MRSA), S. aureus, and P. aeruginosa (Table 2) [35,36].…”
Section: Antibacterial Activity Of Hybrid Amyloidogenic Peptidesmentioning
confidence: 96%
See 3 more Smart Citations